Effect of fiber surface treatment on the incorporation of carbon nanotubes and on the micromechanical properties of a single-carbon fiber-epoxy matrix composite - M. F. Munoz-Velez; A. Valadez-Gonzalez; P. J. Herrera-Franco (eXPRESS Polymer Letters)
Multiwall carbon nanotubes (MWCNTs) previously treated with a cationic polymer were incorporated on the surface of carbon fibers modified by three different chemical treatments, namely, oxidation, oxidation-silanization and oxidation-pre-impregnation. Prior to the incorporation of the MWCNTs, the physical surface properties of the fibers were studied by contact angle and the chemical surface properties by X-ray photoelectron spectroscopy (XPS). The interfacial shear strength (IFSS) of the different systems carbon fiber-MWCNTs-matrix was evaluated using the single-fiber fragmentation test (SFFT) and it was observed that the IFSS of the oxidized-pre-impregnated fibers, was considerably higher than that observed for the other fiber-matrix systems. This was attributed to enhanced interfacial interactions because the fiber surface treatments improved the wettability of the carbon fiber and the MWCNTs, which resulted in a better fiber-matrix mechanical interlocking and to the formation of covalent bonds between the different phases of the composite.